Therapeutic Efficacy of Febuxostat and Allopurinol on Gout Induced Model in Broiler Chicks - Rathod, R.C.; Joshi, B.P.; Ghodasara, D.J.; Dave, C.J.; Patel, M.K.; Raval , Disha Y. (Indian Journal of Veterinary Sciences and Biotechnology, 2018)
This work was conducted to evaluate the comparative therapeutic efficacy of febuxostat and allopurinol on gout induced model in broiler chicks. A total of 108, day-old broiler chicks of either sex were equally divided into six groups, each of 18 birds and numbered from I to VI. Group I was kept as control group, while group II received diclofenac @ 10 mg/kg b wt by oral gavage daily once for 21 days. Group III and IV received febuxostat and allopurinol @ 4 mg/kg and 25 mg/kg b wt daily once, while Group V and VI were treated with febuxostat and allopurinol along with diclofenac @10 mg/kg b.wt. daily once for 21 days. Broiler chicks in all six groups were fed with broiler pre-starter and starter feed ad libitum. The group II (diclofenac) showed clinical sings like dullness, depression and lethargy with shrunken eyes along with 27.77% mortality, and also showed decreased body weight during experiment. The birds from group V and VI also showed clinical signs like dullness, depression and sleepy appearance before death, with 5.55% and 11.11% mortality, respectively. The serum biochemical parameters, viz., Uric acid, Creatinine and BUN values were increased in the diclofenac treated group II which was lowered by the febuxostat and allopurinol treatment in the group V and VI. The birds which were sacrificed at weekly interval did not show any appreciable gross and histopathological lesions, whereas the birds died during experiment showed gross and microscopic lesions which were specific to visceral gout.